Alyaat Alzawayid in the Noble Qur’an, its Conditions and the Ten Doctrines of the Reciters Therein, Through Shatibiya and Al-Durra (Islamic Sciences Journal, 2023)
This study aimed to simplify the topic of Alyaat Alzawayid to make it accessible to scholars and researchers, by explaining the concept of Alyaat Alzawayid, explaining its characteristics and  numbers, and revealing the differences between readers in their reading. The study relied on the deductive method in tracing the placements of the Alyaat Alzawayid in the Noble Qur’an, and the descriptive method for their distribution and classification. The analytical method was used in a simple way to explain some partial differences between scholars in their approach to these Yaat. The study came out with several results, the most important of which are: The diversity of aspects in which readers read some of the words of the Noble Qur’an is one aspect of its miracles. The study revealed the extent of Muslims' interest in this dear book, through direct oral reception, which resulted in interest in the novel and the connected bond with the novel, which confirms that this book is fraught with the care and preservation of Allah. The study also showed the characteristics of Alyaat Alzawayid and their conditions, and how to read them among the ten readers.
Keywords: Yat, appendices, readings, Shattip, deletion and proof .